POLICY OPTIONS FOR ENHANCING WOMEN’S PARTICIPATION IN MANAGING WATER RESOURCES IN KAJIADO COUNTY, KENYA - Gathagu, Teresia W.; Agwata, Jones F. (International Journal of Development Research, 2014)
The important role that women play in the management of water resources has been recognized in various parts of the world. This is because they play a significant role in accessing water for various uses such as washing, cooking, watering of crops and livestock rearing. Their effective participation in water management is however influenced by existing policy, institutional and legal frameworks. In this study, the various policies that enhance women’s participation in water resources management in Kajiado County of Kenya were evaluated from the perspective of relevance, value and limitations. This was done with a view to suggesting practical measures to ensure the women’s important and critical roles are properly captured in the proposed policies on water resources management in the County and elsewhere in the country. The findings show that although the existing policies, legal and institutional frameworks are fairly comprehensive in addressing women’s roles in the management of water resources, the policies do not, however, directly and adequately address women’s issues and concerns in water resources management in the County.
Keywords: policy; women; participation; water management